The Implementing the Problem-Based Learning (PBL) Approach to Enhance Student Engagement and Learning Outcomes in Informatics for Grade X Mechanical Engineering Students at SMK Negeri 2 Karanganyar - Wulansari, Puput; Efendi, Agus; Sulistiyo, Budi (Journal of Global Hospitality and Tourism Technology, 2025)
Enhancing student participation and learning outcomes largely depends on the instructional strategies employed. This study was conducted to explore the implementation of a teaching method. In Grade 10 of the Mechanical Engineering Department at SMK Negeri 2 Karanganyar, the use of Problem-Based Learning (PBL) has proven effective in increasing student participation and academic achievement in the Informatics subject. The aim of this research is to evaluate students’ responses to the teaching of Programming Language in Grade 10 Mechanical Engineering at SMK Negeri 2 Karanganyar using the PBL approach, as well as to improve student participation and learning outcomes through the application of PBL.This study employed a classroom action research method with a quantitative approach. Data were collected through tests and observations, with instruction used as the research instrument. Data were analyzed both descriptively and quantitatively. In Cycle I, student participation in learning activities reached 79.17%, which increased to 85.83% in Cycle II. The participation rate in Meeting 1 was 80.0%, and 79.0% in Meeting 2, reflecting efforts to enhance student learning outcomes during Cycle I. In Cycle II, participation increased to 80.0% in Meeting 1 and 90.6% in Meeting 2. A participation rate of 90.6% indicates a positive response to the learning activities using the PBL approach, showing a significant improvement in this aspect.